2021
DOI: 10.1016/j.tranon.2021.101109
|View full text |Cite
|
Sign up to set email alerts
|

A novel tailored immune gene pairs signature for overall survival prediction in lower-grade gliomas

Abstract: Highlights The Immune-related gene pairs (IRGPs) pronostic signature for LGG is correlated with immune cells infiltration. WGCNA presented a gene set correlating with immune cells infiltration and genes co-expression relationships were visualized. The nomogram constrcted by three IRGPs and clinical factors is a novel tailored tool for individual-level prediction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…One possibility is that NRG3 is able to suppress or otherwise modulate NRG1-mediated activation of ERBB4-positive cells. In our TCGA data analysis, NRG3 showed reduced expression in grade 4 tumors, and low expression was associated with worse OS in IDHmut astrocytomas both in univariate and multivariate analysis, consistent with previous reports on its prognostic role in diffuse glioma in general [ 57 59 ]. Our results clearly linked the gene to IDHmut astrocytoma progression to grade 4.…”
Section: Discussionsupporting
confidence: 91%
“…One possibility is that NRG3 is able to suppress or otherwise modulate NRG1-mediated activation of ERBB4-positive cells. In our TCGA data analysis, NRG3 showed reduced expression in grade 4 tumors, and low expression was associated with worse OS in IDHmut astrocytomas both in univariate and multivariate analysis, consistent with previous reports on its prognostic role in diffuse glioma in general [ 57 59 ]. Our results clearly linked the gene to IDHmut astrocytoma progression to grade 4.…”
Section: Discussionsupporting
confidence: 91%
“…Studies already show evidence about gene signatures, such as autophagy genes related, strongly associated with six immune cell infiltrates (macrophages M0 and M1, Neutrophils, T cells CD8, T cells follicular helper, T cells reg) in LGG (Quan et al, 2021). Additionally, other gene signatures, such as immune-related genes, demonstrate positive and negative correlations with several immune cell infiltrates in LGG (macrophages, dendritic cells, B cells, and CD4 T cells) (Pan et al, 2021). In the same way, our study showed positive and negative correlations with immune infiltrates in LGG, with monocyte, NK, and B cells, T cell CD4+, macrophage (M1 and M2), and myeloid dendritic cells.…”
Section: Discussionmentioning
confidence: 99%